Giving Increased Value to Invertebrates through Ecotourism. - AK Mohd Rafiq AK Matusin; Fiffy Hanisdah Saikim; Norazah Mohd Suki; Mahadimenakbar Mohamed Dawood (International Institute of Chemical, Biological & Environmental Engineering (IICBEE), 2014)
Invertebrates form an estimated 73.5 % of life on earth and are often considered to be most significant component of biodiversity in terms of their diversity and role in ecosystem functioning. Conservation measures for invertebrates are largely inadequate. Conservation efforts can be improved in the context of ecotourism. This paper seeks to determine and examine the overview of response of tourist to the concept of inclusion of invertebrate’s information in ecotourism activities, to obtain an overview of the current levels of the inclusion of information on invertebrates in certain types of ecotourism activities and to provide recommendations on how to address the lack of invertebrate information in ecotourism.